Factors associated with anemia among women of the reproductive age group in Thatta district: study protocol - Sumera Aziz Ali; Zahid Abbasi; Anam Feroz; K Michael Hambidge; Nancy F Krebs; Jamie E Westcott; Sarah Saleem (BMC, 2019)
Abstract Background Maternal anemia is a leading public health issue placing pregnant women at higher risk of low birth weight, preterm birth, perinatal mortality, and neonatal mortality. Women in developing countries are at higher risk of anemia which could be either due to micronutrient deficiencies, hemoglobinopathies, infections or other socio-demographic factors. Thus, it is highly essential to explore the factors of anemia among women of the reproductive age group in order to design suitable interventions. The primary objective of this study is to assess the biological and socio-demographic factors that are associated with anemia among the women of the reproductive age group in Thatta district. Methods An exploratory mixed method study using quantitative and qualitative approaches will be conducted in district Thatta Pakistan from September 2018 to January 2019. In the qualitative phase, data will be collected through focus group discussions and key informant interviews to understand the perceptions of women, their husbands and healthcare providers about anemia. In addition, a quantitative approach using cross-sectional study will be conducted to determine biological and socio-demographic factors associated with anemia. Approximately 150 non-pregnant women and their spouses will be included in the quantitative component of the study. In addition to thematic analysis for the qualitative component, Logistic regression will be done to calculate adjusted Odds ratios with their respective 95% CIs to assess the factors associated with anemia. Discussion The better understanding of biological, socio-demographic factors and community perceptions of anemia will help us to design strategies and interventions to better address anemia during the reproductive cycle in rural areas of Pakistan. This will help the researchers and policymakers to take the appropriate action accordingly by designing suitable approaches to address the specific type of anemia in the rural population of Pakistan. This will, in turn, reduce the chances of adverse maternal and fetal outcomes associated with anemia.